PEMANFAATAN MEDIA E-LEARNING EDLINK UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATERI SISTEM PENCERNAAN MANUSIA - Valleri Rehan Prima Vincinzo; Dyah Astriani (PENSA: E-JURNAL PENDIDIKAN SAINS, 2022)
The purpose of this research was to determine the improvement of critical thinking skills and student responses to the use Edlink e-learning media on the human digestive system materials. This research uses a pre experimental design method with a One Group Pretest-Posttest. The research was conducted at SMP Negeri 46 Surabaya involving students in class VIII-A (experimental class) and class VIII-B (replication class). The results showed that the use of Edlink e-learning media could improve students critical thinking skills. The increase in the percentage of students critical thinking in class VIII-A in the medium category is 62.07% and the high category is 37.93%. Class VIII-B experienced an increase in the percentage of critical thinking in the low category of 3.35%, medium category 62.07%, and high category 34.48%. The results of student responses gave a positive response. Students feel happy, enthusiastic, and interested in taking part in learning activities using the Edlink e-learning media. Thus, the use of Edlink e-learning media makes online learning more meaningful so that students critical thinking skills increase.